2018
DOI: 10.3389/fgene.2018.00451
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Evolution of Pseudomonas aeruginosa Resistance to Ribosome-Targeting Antibiotics

Abstract: The present work examines the evolutionary trajectories of replicate Pseudomonas aeruginosa cultures in presence of the ribosome-targeting antibiotics tobramycin and tigecycline. It is known that large number of mutations across different genes – and therefore a large number of potential pathways – may be involved in resistance to any single antibiotic. Thus, evolution toward resistance might, to a large degree, rely on stochasticity, which might preclude the use of predictive strategies for fighting antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 88 publications
(119 reference statements)
6
76
0
Order By: Relevance
“…The reported increasing penicillinase-producing β-lactamases strains among these organisms validates the noticeably observable high rate resistance of our isolates to piperacillin [42]. Antibiotic resistance is a public health menace with an alarming proportion that is getting collective attention more so that several studies have found a correlation between level of antibiotic prescription with the prevalence of antibiotic resistance [43][44]. Patients with resistant P. aeruginosa infections have a poor prognosis hence it is imperative that P. aeruginosa strains presenting severe drug resistance is monitored [23].…”
Section: Discussionsupporting
confidence: 75%
“…The reported increasing penicillinase-producing β-lactamases strains among these organisms validates the noticeably observable high rate resistance of our isolates to piperacillin [42]. Antibiotic resistance is a public health menace with an alarming proportion that is getting collective attention more so that several studies have found a correlation between level of antibiotic prescription with the prevalence of antibiotic resistance [43][44]. Patients with resistant P. aeruginosa infections have a poor prognosis hence it is imperative that P. aeruginosa strains presenting severe drug resistance is monitored [23].…”
Section: Discussionsupporting
confidence: 75%
“…While A. baumannii has one copy of fusA1 , P. aeruginosa and other Pseudomonas species also harbor an additional copy encoded by the gene fusA2 (Palmer et al, 2013). EF-G is not known to be a direct binding target of TOB, and has received little attention as a mechanism of resistance to aminoglycosides in these species (Bolard et al, 2017; Sanz-García et al, 2018). However, this protein is the direct binding target of other antibiotics including fusidic acid and argyrin B (Johanson and Hughes, 1994; Jones et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The exact mechanism by which mutations in EF-G confer aminoglycoside resistance is currently unknown but this study demonstrates it is an important resistance determinant. The ptsP gene encodes phosphoenolpyruvate phosphotransferase protein, which is part of the nitrogen phosphotransferase system and has previously been identified as a target of aminoglycoside resistance for P. aeruginosa , but not A. baumannii (Sanz-García et al, 2018; Schurek et al, 2008). The mechanism by which mutations in ptsP may confer resistance to TOB is also unknown, although the nitrogen phosphotransferase system has been shown to regulate expression of genes responsible for coordinating the antibiotic stress response, suggesting an indirect link between the nitrogen phosphotransferase system and antibiotic resistance (Gebhardt and Shuman, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D). Furthermore, mutations in recycling factor were selected in Pseudomonas aeruginosa evolved for resistance to the TET derivative tigecycline [Sanz-Garcia et al , 2018]. The observed alleviation of TET action by a recycling bottleneck (Fig.…”
Section: Discussionmentioning
confidence: 99%